2000
DOI: 10.1002/(sici)1520-6327(200001)43:1<33::aid-arch5>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase inhibitors from the molting fluid of the pharate adult tobacco hornworm,Manduca sexta

Abstract: The molting fluid of pharate adult Manduca sexta was found to contain at least two types of proteinase inhibitor activities. One inhibited the native cuticle degrading trypsin‐like proteinase, MFP1, while the other was found to be highly specific for subtilisin‐like enzymes. The developmental profiles of both these inhibitor activities were investigated. MFP‐1 inhibitor activity was found to be present in the molting fluid of all stages of pre‐ecdysial development, except stage 7, which possessed the highest l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The moulting fluid of the silkworm Cecropia is characterized by high levels of chitinase and protease activities (Passonneau and Williams, 1953). In the moulting fluid of Manduca sexta high levels of the trypsin-like MFP-1 proteinase have been identified and related to cuticle degrading activities (Samuels and Reynolds, 2000). In our present D. virilis study, we show that prior to pupation the moulting fluid mainly comprises serine proteases, which suddenly disappear.…”
Section: Biological Significance Of the Kil-1 Protein In The Pupationmentioning
confidence: 48%
See 2 more Smart Citations
“…The moulting fluid of the silkworm Cecropia is characterized by high levels of chitinase and protease activities (Passonneau and Williams, 1953). In the moulting fluid of Manduca sexta high levels of the trypsin-like MFP-1 proteinase have been identified and related to cuticle degrading activities (Samuels and Reynolds, 2000). In our present D. virilis study, we show that prior to pupation the moulting fluid mainly comprises serine proteases, which suddenly disappear.…”
Section: Biological Significance Of the Kil-1 Protein In The Pupationmentioning
confidence: 48%
“…We assume it improbable that protein turnover abolishes these proteolytic activities because proteases in extracellular fluids like pupation fluids should be very stable and should require specific developmental control mechanisms at the post-transcriptional level. This assumption is substantiated by the observation that in the moulting fluid of the pharate adult hornworm Manduca sexta, the levels of the trypsin-like protease MFP-1 are inversely correlated with MFP-1-inhibitor activity during development (Samuels and Reynolds, 2000).…”
Section: Biological Significance Of the Kil-1 Protein In The Pupationmentioning
confidence: 91%
See 1 more Smart Citation
“…In case of the chymotrypsin-like peptidase SeCT34 from Spodoptera exigua it has been suggested that the zymogen is activated by chymotrypsin rather than trypsin (Herrero et al, 2005). TcCTLP-5C and TcCTLP-6C may be also targets for regulatory serine peptidase inhibitors that are present in the molting fluid as well (Samuels and Reynolds, 2000). In any case, chymotrypsin-like peptidases apparently act in concert with other molting peptidases to degrade proteins in the old cuticle, which may involve also some of those chymotrypsin-like peptidases that we did not examine so far.…”
Section: Discussionmentioning
confidence: 99%
“…Trypsin may also be the activator of enzymes involved in the degradation of cuticle, such as β-Nacetylglucosaminidase, present in the moulting fluid of insects (Samuels et al 1993) and crustaceans (Warner & Matheson 1998). Klein et al (1996) found that both trypsin mRNA and trypsin enzyme activity are at their highest levels during premoult (stage D1) of the shrimp Penaeus vannamei.…”
Section: Feeding and Digestionmentioning
confidence: 99%